2022
DOI: 10.1111/codi.16032
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of MR identified EMVI, tumour deposits, mesorectal nodes and pelvic side wall disease in locally advanced rectal cancer

Abstract: Aim To study the prognostic significance of MRI identified tumour deposits (TD), extramural vascular invasion (EMVI), lymph node metastases (LNM) and pelvic sidewall (PSW) disease in rectal cancer. Methods This IRB approved study was conducted on patients with stage IIA–IIIC rectal adenocarcinoma treated with neoadjuvant long course chemoradiotherapy (LCCRT) and total mesorectal excision (TME) type of surgery between 2012–2018. A radiologist blinded to outcome reviewed staging and restaging magnetic resonance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 27 publications
(51 reference statements)
0
18
0
2
Order By: Relevance
“…The normal vascular wall around the rectum appears to be linear and zigzag in MRI-T2WI images. However, EMVI shows a tumor signal in the blood vessels, widened vessels, or a tumor that has expanded beyond and destroyed the wall (8).…”
Section: Patient Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The normal vascular wall around the rectum appears to be linear and zigzag in MRI-T2WI images. However, EMVI shows a tumor signal in the blood vessels, widened vessels, or a tumor that has expanded beyond and destroyed the wall (8).…”
Section: Patient Characteristicsmentioning
confidence: 99%
“…In total, 187 patients were enrolled in the study with an average PTV of 16.2±11.1 (2.07-72.68) cm 3 . The longest distance outside the muscularis propria was 3.8±3.1 [1][2][3][4][5][6][7][8][9][10][11][12][13][14] mm; positive correlation with PTV (r=0.581, P<0.001). Based on a PTV best cutoff point of 15 cm 3 (5), the patients were divided into the PTV ≤15 cm 3 group and the PTV >15 cm 3 group, which had 3-year DFS rates of 86.6% and 64.6% (P≤0.001), distant metastasis (DM) rates of 8.9% and 23.0% (P=0.001), and LR rates of 4.7% and 16.7% (P=0.004), respectively.…”
Section: Effects Of Different Factors On Prognosismentioning
confidence: 99%
“…Moreover MRI‐determined TDs/EMVI status is also a significant prognostic factor after neoadjuvant chemoradiotherapy 20,42 . Patients with MRI‐detected TDs/EMVI with a good preoperative treatment response had a prognosis similar to patients with negative TDs/EMVI status at baseline MRI, 20,41,43 whereas persistent TDs and /or EMVI after neoadjuvant treatment led to worse prognosis 22 . Finally, TDs in a neoadjuvant setting might result from tumour regression, reflecting fragmentation or discontinuous eradication of an original tumour with more aggressive biology and would still confer a poor prognosis 24,39,44 .…”
Section: Beyond T N and M: Tumour Deposits In Rectal Cancermentioning
confidence: 99%
“…19 On the other hand it has been reported that current MRI staging based on T and N status does not adequately predict prognosis, whereas MRIdiagnosed EMVI and tumour deposit (TD) status have greater prognostic accuracy and are superior in determining treatment and follow-up protocols. [20][21][22] Then in addition to well-recognized pathological prognostic factors, namely T, N and M included in the classical TNM staging system, identification of novel pathological entities, that is, TDs, should be taken into account in predicting the regional and systemic spread of rectal carcinoma and in the evaluation of treatment strategies. 23,24 This review aims to discuss the impact of TDs on the oncological outcome of patients who undergo TME with LPLND for low rectal carcinoma.…”
Section: Introductionmentioning
confidence: 99%
“…In the detection of extramural vascular invasion(EMVI),MRI has moderate sensitivity and high specificity. However, MRI cannot definitively depict vessels with a diameter of < 3 mm, including micro-arteriovenous and lymphatic vessels [9,10]. Therefore, accurate preoperative imaging evaluation of LVI of rectal cancer is highly challenging.…”
Section: Introductionmentioning
confidence: 99%